Creation of a Surreal Dramatic Text Based on the Myth of Kramat Bedil from Kedotan - Ikhsan Satria Irianto; Dinda Assalia Avero Pramasheilla; Lusi Handayani; Tofan Gustyawan; Dwi Febrianti, Syielvi (Universitas Negeri Medan, 2025)
The myth of Kramat Bedil is a local genius of the Kedotan Village community who has a surreal vision. The creation of a surreal dramatic text based on the myth of Kramat Bedil is an effort to process the cultural wealth of Kedotan Village into a drama that can meet global aesthetic needs. This research is an ethnodramaturgical research oriented towards processing cultural products. The data collection techniques used consist of interviews, observations and literature studies. The data testing technique used is the source triangulation technique. The data analysis techniques used are data reduction techniques, data presentation techniques and conclusion drawing techniques. The drama writing technique used is the writing mechanism of Lajos Agri. The results achieved from this study are surrealistic dramatic texts with a dramatic vision of